Awareness of health risks associated with energy drink consumption among students in Abha City, Saudi Arabia - Rishi Kumar Bharti; Awad Al Samghan; Ayoub Ali Alshaikh; Nimesh Archana; Hayfa Al Hefdhi; Asma Saad Habbas (Global Journal of Medicine and Public Health, 2024)
Introduction Consumption of beverages, especially ones containing caffeine and other stimulants, called ‘energy drinks’, has been recognized as a growing public health problem worldwide. As energy drinks are popular among students, this study aimed to explore students’ awareness of the potential health risks associated with such drinks.